2006
DOI: 10.1186/cc5082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a low-flow veno-venous carbon dioxide removal device: results of an experimental study in adult sheep

Abstract: Introduction Extracorporeal lung assist, an extreme resource in patients with acute respiratory failure (ARF), is expanding its indications since knowledge about ventilator-induced lung injury has increased and protective ventilation has become the standard in ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Using a standardized protocol of ventilation based on the ARDS Net protocol, we were able to demonstrate that our combined RRT + ECC o 2 R system decreased arterial PC o 2 by 21%. This result is similar to that reported with the Decap system, performed at a lower blood flow (300 mL/min) ( 34 ). Although the magnitude of the Pa co 2 reduction is less impressive than in the study by Forster et al ( 35 ), the range of Pa co 2 observed in our study is markedly lower.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using a standardized protocol of ventilation based on the ARDS Net protocol, we were able to demonstrate that our combined RRT + ECC o 2 R system decreased arterial PC o 2 by 21%. This result is similar to that reported with the Decap system, performed at a lower blood flow (300 mL/min) ( 34 ). Although the magnitude of the Pa co 2 reduction is less impressive than in the study by Forster et al ( 35 ), the range of Pa co 2 observed in our study is markedly lower.…”
Section: Discussionsupporting
confidence: 90%
“…The primary endpoint was a 20% reduction in Pa co 2 at 20 minutes after ECC o 2 R initiation ( 34 ). With a mean Pa co 2 before ECC o 2 R of 50 ± 10 Torr, a sample of 10 patients would be required to detect a bilateral difference of 5% with a power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Physical examination, chest radiography, electrocardiography, and standard biological tests often fail to accurately differentiate heart failure (HF) from pulmonary causes of dyspnea (3). Timely differentiation of HF from other causes of dyspnea may permit the early institution of appropriate medical therapy (4)(5)(6). Brain natriuretic peptide (BNP) and amino-terminal pro-brain natriuretic peptide (NT-proBNP) have been proposed as early markers of HF and demonstrated to be useful for diagnosing and excluding HF in emergency department (7)(8)(9).…”
mentioning
confidence: 99%
“…Since ultrafiltrate contains dissolved CO 2 , recirculating in this way allows additional CO 2 removal by creating a greater flow rate through the membrane lung than the flow from the patient. Consequently, smaller membrane lungs can be used (0.3 to 1.35 m 2 ) with lower flow rates (<500 ml.minute -1 ) than conventional ECCOR [33], resulting in similar anticoagulation requirements to continuous venovenous hemodialysis [46]. The Decap has been successfully used in adults and children [9,47,48].…”
Section: Venovenous Carbon Dioxide Removalmentioning
confidence: 99%